Search For Dna Sequences in Orf Finder - P. M., Nasriddinova (American Journal of Biology and Natural Sciences, 2025)
In addition to DNA carrying the genetic information of a living organism or cell, it also plays a crucial role in the formation of amino acids. Before the DNA base sequence is encoded into amino acids, a search for open reading frames (ORFs) occurs. These ORFs form DNA regions potentially capable of being converted into amino acids. Demonstrating the full potential of ORFs in DNA sequences is important because it can aid in genetic analysis research.